Akibat Hukum Perjanjian Pinjam-Meminjam Uang yang Dinyatakan Batal Demi Hukum - Ni Made Ayu Pratiwi; I Nyoman Putu Budiartha; Ni Komang Arini Styawati (Warmadewa Press, 2021)
The money lending and borrowing agreement is an agreement involving the debtor and the creditor. In this type of agreement, there is usually what is called a null and void agreement. This research uses a method based on a statutory and conceptual approach. Sources of data used are primary and secondary legal materials with library research. The technique of collecting data is by recording, quoting, summarizing and then reviewing documents in the form of laws and regulations, literature, magazines, newspapers, and other articles related to the object of research. The material is presented descriptively, namely in the form of written or oral words from the informants relating to the issues discussed so that conclusions can be explained. The purpose of this research is to find out the loan and loan agreement which is declared null and void and the legal consequences for the parties of the agreement which are null and void. The results of the analysis found that the occurrence of a null and void agreement in a money loan agreement. A null and void agreement can occur because the objective requirements stipulated in the law are not fulfilled and the legal consequences for the parties are not clearly written in the rules of the Civil Code, where in The regulation only contains the loan and loan agreement and the validity of an agreement does not discuss the sanctions for the parties in the event of a null and void agreement